Religious Moderation and Transnational Islamic Ideology: Phenomena and Implications in Indonesia - Aderus, Andi; Ambo Masse, Rahman; Rahman, Amri; Syam, Aydi; Mohammad Subaeh, Syekh Toha Nasir; Firman, Firman (Ulumuna, 2024)
This research analyzes Islamic transnational movements, especially the Salafi in South Sulawesi, their internalization, and implications for religious moderation. By applying qualitative methods and a phenomenological approach, this research was carried out in several key locations in South Sulawesi, namely in Makassar, Gowa, and Parepare, including Islamic boarding schools and several strategic mosques. The research reveal that the Salafi da'wah approach, which is effective and responsive to social dynamics, has gained a place in society. However, this puritanical approach faces challenges internalizing religious moderation, especially in interreligious tolerance and adaptation to local culture. Religious moderation offers a solution to create more inclusive and adaptive religious behavior, supporting harmony between religious communities in Indonesia.